HUBUNGAN EFIKASI DIRI AKADEMIK DENGAN STUDENT ENGAGEMENT PADA MAHASISWA FSM UNDIP YANG BEKERJA PARUH WAKTU - AR-RUUM AKHIRA RUFAIDA; Unika Prihatsanti (Jurnal EMPATI, 2017)
The aims of this research is to determine the correlation between academic self efficacy and student engagement in FSM UNDIP part-time collage student. The population of this research is part-time collage student in FSM UNDIP with 60 collage student as sample and selected using convenience sampling. The technique of collecting data uses Likert scale psychology that consist of two scales, which are academics self-efficacy (35 aitems, α =  .939) and student engagement (21 items, α = 0,876). Data analysis uses simple regression analysis with the help of SPSS version 21.0. The result shows correlation coefficient .544  and p = .000 (p <.05) this result means  there is a positive correlation between academic self efficacy and student engagement in FSM UNDIP part-time collage student.  Correlation coefficient value indicates there is a significant correlation, it means the more positive academic self efficacy, the higher student engagement. The value of determination coefficient is .295, this value shows that parental social affect self efficacy in amount of 29,5%.